Living in difficult conditions: an analysis of the factors associated with resilience in youth of a disadvantaged city - YORGUNER, NEŞE; TOPÇUOĞLU, VOLKAN (TAYLOR & FRANCIS LTD, 2019)
OBJECTIVE: Children and adolescents facing difficult life circumstances due to social, economic and cultural adversity, form a disadvantaged group in terms of social functioning and healthy psycho-social development. The goal of this study was to evaluate the psychological resilience of high school students in Mu City - which was ranked last in the general life index among 81 provinces according to 2015 data from the Turkish Statistical Institute - and to examine different dimensions of psychological resilience in relation to a variety of variables including adverse life events and demographic characteristics. METHOD: The study sample consisted of 1025 students from the 10th and 11th grades of five different high schools operating in the city centre of Mu. Participants were asked to fill in a socio-demographic questionnaire, the List of Adverse Life Events and the 59-item Resilience and Youth Development Module (RYDM). A series of correlational and descriptive analyses were then performed. RESULTS: Correlational analyses revealed that among the demographic factors, low economic status, a criminal record and poor academic performance were associated with poor psychological resilience, while among adverse life events, the deterioration of parental economic status, frequent arguments between parents as well as a history of mental illness and alcohol/substance abuse in the family were also linked to low levels of psychological resilience. It was also determined that girls had higher scores on internal assets of RYDM (empathy, problem solving, self efficacy, communication and cooperation, goals, self awareness and educational aspirations), while exposure to a larger number of adverse life events negatively affected internal resilience assets. Finally, trauma exposure, just as the low RYDM scores, seems to be associated with frequent arguments between parents, alcohol/substance abuse in the family, male gender and a criminal record. However, there was no significant relationship between psychological resilience and trauma alone. CONCLUSION: Interventions to improve psychological resilience, which is a dynamic process, need to be comprehensive and multi-dimensional. In this context, it is crucial to elucidate the factors associated with the psychological resilience of children and adolescents exposed to a specific risk factor, such as adverse living conditions. In order to improve our understanding of psychological resilience and youth development in Turkey and to determine specific needs for interventions, future studies on various risk groups in different pilot cities - as in the example of Mu - are needed.
Keywords: Resilience; adverse life events; adolescent; risk groups; trauma; protective factors; LIFE EVENTS; SOCIOECONOMIC-STATUS; PSYCHOLOGICAL RESILIENCE; ACADEMIC-ACHIEVEMENT; CHILDREN; RISK; CHILDHOOD; MIGRATION; PSYCHOPATHOLOGY; ADOLESCENTS